(3GdeGdjI GdOhdjI (B/s - (3GdbQjTj, eMeO UGdMs ((3YeGf(B: s (3eDSSI GdhQGb(B, s, 2007)
(3JgJe GdeGdjI GdOhdjI HGdGHYGO GdchfjI ddGShGb hGdeDSSGJ hGdGOhGJ hGdGSGdjH hbVGjG GdSjGSI GdYGeI GdJj JfTC ef GdGShGb hGdGSGdjH , hGdeGdjI GdMOjKI JJVef OQGSI SYQ GdUQa GdGLfHj hGSJYeGd GdGShGb GdOhdjI eKd GShGb GdYedI GdGhQhHjI , hGShGb GdSfOGJ GdGhQhHjI ,Gf OQGSI GdGbJUGO GdOhdj aj GdYUQ GdMOjK dG JYJeO Ydi fXQjI heTcdGJ GdJLGQI Hjf GdGbWGQ GdeNJdaI Hd GUHMJ GdYdGbGJ Hjf GdOhd JYJeO Ydi GdGYJHGQGJ GdeGdjI Gdi LGfH GdbVGjG GdJLGQjI , hjTJed GdcJGH Ydi NeSI YTQ aUdG (B: (3JfGhdJ ebOeI aj GdeGdjI GdOhdjI , hehVhY GdfbhO heYGOdGJ GdUQa GdGLfHj , ceG PcQ OQGSI SYQ GdUQa GdeMOO ebOeG hGdhbGjI ef eNGWQ GdUQa GdGLfHj , hOQGSI dejRGf GdeOahYGJ fXQjI heaGgje , hJWQb Gdi GdGbJUGO Gdcdj GdOhdj ddJYQa Ydi GTJbGb efMfi ejRGf GdeOahYGJ ef efMfi (B(IS) (3, hGSJYQV GjVG GdfXGe GdfbOj GdOhdj JGQjNG heDSSGJ hJZjQGJ , hJfGhd ehVhYGJ NUGFU h gjcd GdUjQaI GdOhdjI(B/(3GdGSJKeGQ GdGLfHj GdeHGTQ h GdJehjd GdOhdj(B/(3Shb GdYedI GdGhQhHjI(B/(3GdGShGb GdeGdjI GdOhdjI(B/(3GdGReGJ GdOhdjI GdeGdjI(B/(3GdGOhGJ GdLOjOI aj GdeGdjI GdYGeI (B/(3GdeGdjI GdchfjIs
(3HjHdjhZQGajG U(B.285s
Keywords: (3GdJehjd GdOhdjs; (3GdSjGSI GdeGdjIs; (3GdeGdjI GdYGeIs